Fundamentals of polarimetric remote sensing - Schott, John R., 1951- (Bellingham : SPIE, 2009)
This text is for those who need an introduction to polarimetric signals to begin working in the field of polarimetric remote sensing, particularly where the contrast between manmade objects and natural backgrounds are the subjects of interest. The book ta
Includes bibliographical references and index.
Keywords: Polarimetric remote sensing; Polarimetrik uzaktan algılama; Infrared imaging; Kızılötesi görüntüleme; Reflection (Optics) Polarimetry; Yansıma (Optik) Polarimetresi